Fleece qualities of menemen sheep: i. morphologic and physical qualities - Günnur Peşmen; Mehmet Yardımcı (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to determine the physical and morphological properties of fleece from Menemen sheep and to use this data for breeding and reform of Menemen sheep. Materials and Methods: This study was carried out on 98 Menemen sheep in a private company established in Karacaören area, Şuhut Town in Afyonkarahisar. Results: The results for greasy fleece weight, post-shearing live weight, clean fleece percentage, fineness, length, elasticity and strength were 1583.78 g, 51.68 kg, 66.78%, 30.91 μm, 36.35 mm, 32.60% and 20.69 cN/tex, respectively in Menemen ewes. Conclusion: Menemen fleece can be used as rawmaterial for carpet manufacturing. Moreover it can be observed that through reform study, fleece in fabric quality can be achieved. 1Emirdağ Meslek